Organic fertilization regimes suppress fungal plant pathogens through modulating the resident bacterial and protistan communities. Issue 1 (11th March 2022) - Sun, Anqi; Jiao, Xiaoyan; Ren, Peixin; Yu, Danting; Li, Fangfang; Chen, Qing‐Lin; Bi, Li; He, Ji‐Zheng; Hu, Hang‐Wei
Abstract: Introduction: Fungal plant pathogens are an emerging threat to economically important crop production worldwide and a significant risk to global food security. However, we have limited knowledge of how agricultural management practices drive the emergence and spread of pathogens within crop microbiomes and the underlying ecological mechanisms. Materials and Methods: We characterized the profiles of potential fungal plant pathogens, as well as bacterial and protistan communities, in sorghum phyllosphere, root endosphere, and rhizosphere and bulk soils collected from a long‐term experiment with multiple inorganic and organic fertilization regimes. Results: We found contrasting patterns of fungal plant pathogens across the four sorghum–soil compartments and that organic fertilization regime significantly reduced the diversity and proportions of fungal plant pathogens in rhizosphere and bulk soils. We further found that the changes in fungal plant pathogens were driven more by resident bacterial and protistan communities than by soil physicochemical parameters. There was a significantly negative relationship between the diversity of fungal plant pathogens in the rhizosphere and bulk soils with sorghum yield and protein contents. Structural equation modeling revealed that long‐term organic fertilization regimes contributed to the suppression of fungal plant pathogens mainly through modulating the resident bacterial and protistan communities. Conclusion: These findings advance our understanding of the responses of fungal plant pathogens in crop microbiomes to fertilization regimes, with implications for more targeted strategies to manage the impacts of fungal pathogens on plant health and economic losses.